The wellbeing of education professionals: an exploratory study on Second-Career Teachers - Frison, Daniela (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2024)
Numerous studies in the literature investigate working conditions and factors of stress and burnout in the teaching profession. Opposite, an overview of the literature on no-teaching educational professions shows that only a few studies investigate the low attractiveness of the profession and factors supporting or hindering the wellbeing of professionals. The paper focuses on a target audience that, while deferring to the school sector, deviates from the profile of the traditional teacher: the Second-Career Teacher (SCT). After framing the research design adopted by the SecWell - Second Career Teachers Wellbeing project, the paper presents the results concerning advantages, disadvantages, and barriers in entering the profession and performing it as a second career according to in-service and pre-service SCTs.